The welfare of cattle - Engle, Terry (Terry Eugene), 1971- (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
Contains a selection of White Papers, commissioned to better inform the exploration of cattle welfare. These are prepared by notable experts in their field, to help provide factual context around selected topics that impact cattle welfare and production systems. Covers all aspects of cattle use in an accessible style, making this a must have volume for anyone interested in cattle welfare or cattle medicine. Provides an in-depth picture of the distinctive beef and dairy cattle welfare practices and issues, covering topics such as behavior, breeding and genetic manipulation, nutrition and feeding, housing and management, health and disease, and transport and slaughter. Written by acknowledged leaders in animal science, veterinary science, philosophy and animal welfare, presenting a truly multidisciplinary perspective on cattle welfare. Includes a section on understanding and managing animal welfare in both beef and dairy cattle, discussing how cattle perceive the world, animal handling and pain mitigation, and how to assure that the cows have a reasonably good life. The Welfare of Cattle offers an accurate, detailed account of the ethical and welfare concerns related to the human use of cattle. There is currently no significant book dealing with the welfare of cows, animals often seen as archetypal paradigms of 'farm animals'. Covering both beef and dairy cattle, the expert authors provide in-depth information on the husbandry roots of traditional agriculture, the replacement of this system of stewardship by an industrial model, and the resulting welfare challenges associated with industrial agriculture: feedlots, highly industrialized dairies, and slaughterhouses killing huge numbers of animals who have been transported great distances. This important book explores in detail the ways in which people who are providing care for cattle can take their first step, or their next step, toward enhancing the welfare of these animals.
OCLC-licensed vendor bibliographic record.
Keywords: Cattle; Animal welfare; MEDICAL / Veterinary Medicine / Food Animal; TECHNOLOGY / Agriculture / General; TECHNOLOGY / Food Science